gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Emydomyces testavorans DNA is detected from shell swabs of companion chelonians - Timothy J. Brunner; Amanda D. Wong; Laura Adamovicz; Amber Simmons; Emilie Ospina; Krista A. Keller (Journal of Exotic Pet Medicine, 2024)

Climatic drivers and tree growth in a key production species: The case of Cryptomeria japonica (Thunb. ex L.f.) D.Don in the Azores archipelago - D.C. Pavão; D. Brunner; R. Resendes; J. Jevšenak; L. Borges Silva; L. Silva (Dendrochronologia, 2024)

Verification of the Fourier-enhanced 3D finite element Poisson solver of the gyrokinetic full-f code PICLS - A. Stier; A. Bottino; M. Boesl; M. Campos Pinto; T. Hayward-Schneider; D. Coster; A. Bergmann; M. Murugappan; S. Brunner; L. Villard; F. Jenko (Computer Physics Communications, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Utility of wastewater genomic surveillance compared to clinical surveillance to track the spread of the SARS-CoV-2 Omicron variant across England - Franziska S. Brunner; Alexander Payne; Edward Cairns; George Airey; Richard Gregory; Natalie D. Pickwell; Myles Wilson; Matthew Carlile; Nadine Holmes; Verity Hill; Harry Child; Jasmine Tomlinson; et al. (Water Research, 2023)

Forestry in the Face of Global Change: Results of a Global Survey of Professionals - Austin Himes; Jürgen Bauhus; Shankar Adhikari; Saroj Kanta Barik; Hugh Brown; Andreas Brunner; Philip J. Burton; Lluís Coll; Anthony W. D’Amato; Jurij Diaci; Yonten Dorji; Ernest G. Foli; et al. (Current Forestry Reports, 2023)
Purpose of Review Forests support most global terrestrial biodiversity and contribute to the livelihood of billions of people, but these and other benefits are in jeopardy due to global change. This leads to questions, such as how to address the challenges of global change in forest management, given the lack of knowledge and deep uncertainty about future developments. In addition, many of the impediments to implement adaptation strategies are unknown. Recent Findings Here, we present an overview of results from a global survey of 754 forestry professionals (370 researchers and educators, 227 practicing foresters, 37 policymakers, 64 administrators, and 56 with other or unspecified roles) from 61 countries across 6 continents who were interested in global change issues. These professionals were asked about their opinion regarding three different adaptation strategies: resist , adapt , and transform . Most respondents agreed that the majority of global change factors will negatively influence the ability of forests to provide desired ecosystem services. Similarly, they agreed about major challenges when implementing adaptation strategies and specifically whether our current knowledge base is sufficient. These concerns were not limited to ecological aspects, but respondents also highlighted the need for a better appreciation of social/political and economic barriers, especially regarding transformation strategies. In addition, the response patterns, including differences due to economic status, highlight the importance of developing and evaluating adaptation strategies in a local social–ecological context. Summary Our study demonstrates a widespread perception on the part of forestry professionals around the world, especially among researchers and practitioners, that many global change factors will affect sustainable forest management negatively, resulting in the need for active silvicultural adaption. The results also suggest potential barriers to different adaptation strategies, particularly a relative lack of information and social acceptance for transform strategies. Further, this study highlights the importance of social and political factors and the need to understand the general public’s values regarding adaptation strategies as well as how the influence of public opinion is perceived by forest managers.

G × E interactions as a basis for toxicological uncertainty - Ilinca Suciu; David Pamies; Roberta Peruzzo; Petra H. Wirtz; Lena Smirnova; Giorgia Pallocca; Christof Hauck; Mark T. D. Cronin; Jan G. Hengstler; Thomas Brunner; Thomas Hartung; Ivano Amelio; et al. (Archives of Toxicology, 2023)
To transfer toxicological findings from model systems, e.g. animals, to humans, standardized safety factors are applied to account for intra-species and inter-species variabilities. An alternative approach would be to measure and model the actual compound-specific uncertainties. This biological concept assumes that all observed toxicities depend not only on the exposure situation (environment = E), but also on the genetic (G) background of the model (G × E). As a quantitative discipline, toxicology needs to move beyond merely qualitative G × E concepts. Research programs are required that determine the major biological variabilities affecting toxicity and categorize their relative weights and contributions. In a complementary approach, detailed case studies need to explore the role of genetic backgrounds in the adverse effects of defined chemicals. In addition, current understanding of the selection and propagation of adverse outcome pathways (AOP) in different biological environments is very limited. To improve understanding, a particular focus is required on modulatory and counter-regulatory steps. For quantitative approaches to address uncertainties, the concept of “genetic” influence needs a more precise definition. What is usually meant by this term in the context of G × E are the protein functions encoded by the genes. Besides the g ene sequence, the regulation of the gene expression and function should also be accounted for. The widened concept of past and present “ g ene expression” influences is summarized here as G e . Also, the concept of “environment” needs some re-consideration in situations where exposure timing (E t ) is pivotal: prolonged or repeated exposure to the insult (chemical, physical, life style) affects G e . This implies that it changes the model system. The interaction of G e with E t might be denoted as G e × E t . We provide here general explanations and specific examples for this concept and show how it could be applied in the context of New Approach Methodologies (NAM).

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Canine distemper virus in the Serengeti ecosystem: molecular adaptation to different carnivore species - Veljko M. Nikolin; Ximena A. Olarte‐Castillo; Nikolaus Osterrieder; Heribert Hofer; Edward Dubovi; Camila J. Mazzoni; Edgar Brunner; Katja V. Goller; Robert D. Fyumagwa; Patricia D. Moehlman; Dagmar Thierer; Marion L. East (Molecular Ecology, 2017)
Was the 1993/1994 fatal canine distemper virus ( CDV ) epidemic in lions and spotted hyaenas in the Serengeti ecosystem caused by the recent spillover of a virulent domestic dog strain or one well adapted to these noncanids? We examine this question using sequence data from 13 ‘Serengeti’ strains including five complete genomes obtained between 1993 and 2011. Phylogenetic and haplotype network analyses reveal that strains from noncanids during the epidemic were more closely related to each other than to those from domestic or wild canids. All noncanid ‘Serengeti’ strains during the epidemic encoded: (1) one novel substitution G134S in the CDV ‐V protein; and (2) the rare amino acid combination 519I/549H at two sites under positive selection in the region of the CDV ‐H protein that binds to SLAM ( CD 150) host cell receptors. Worldwide, only a few noncanid strains in the America II lineage encode CDV ‐H 519I/549H. All canid ‘Serengeti’ strains during the epidemic coded CDV ‐V 134G, and CDV ‐H 519R/549Y, or 519R/549H. A functional assay of cell entry revealed the highest performance by CDV ‐H proteins encoding 519I/549H in cells expressing lion SLAM receptors, and the highest performance by proteins encoding 519R/549Y, typical of dog strains worldwide, in cells expressing dog SLAM receptors. Our findings are consistent with an epidemic in lions and hyaenas caused by CDV variants better adapted to noncanids than canids, but not with the recent spillover of a dog strain. Our study reveals a greater complexity of CDV molecular epidemiology in multihost environments than previously thought.

A decade of irrigation transforms the soil microbiome of a semi‐arid pine forest - Martin Hartmann; Ivano Brunner; Frank Hagedorn; Richard D. Bardgett; Beat Stierli; Claude Herzog; Xiamei Chen; Andreas Zingg; Elisabeth Graf‐Pannatier; Andreas Rigling; Beat Frey (Molecular Ecology, 2017)
The impact of climate change on the soil microbiome potentially alters the biogeochemical cycle of terrestrial ecosystems. In semi‐arid environments, water availability is a major constraint on biogeochemical cycles due to the combination of high summer temperatures and low rainfall. Here, we explored how 10 years of irrigation of a water‐limited pine forest in the central European Alps altered the soil microbiome and associated ecosystem functioning. A decade of irrigation stimulated tree growth, resulting in higher crown cover, larger yearly increments of tree biomass, increased litter fall and greater root biomass. Greater amounts of plant‐derived inputs associated with increased primary production in the irrigated forest stands stimulated soil microbial activity coupled with pronounced shifts in the microbiome from largely oligotrophic to more copiotrophic lifestyles. Microbial groups benefitting from increased resource availabilities (litter, rhizodeposits) thrived under irrigation, leading to enhanced soil organic matter mineralization and carbon respired from irrigated soils. This unique long‐term study provides new insights into the impact of precipitation changes on the soil microbiome and associated ecosystem functioning in a water‐limited pine forest ecosystem and improves our understanding of the persistency of long‐term soil carbon stocks in a changing climate.

Calf muscle perfusion as measured with magnetic resonance imaging to assess peripheral arterial disease - Gerd Brunner; Jean Bismuth; Vijay Nambi; Christie M. Ballantyne; Addison A. Taylor; Alan B. Lumsden; Joel D. Morrisett; Dipan J. Shah (Medical & Biological Engineering & Computing, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Experimental influence of pH on the early life-stages of sea urchins II: increasing parental exposure times gives rise to different responses - Coleen C. Suckling; Melody S. Clark; Christine Beveridge; Lars Brunner; Adam D. Hughes; Elizabeth M. Harper; Elizabeth J. Cook; Andrew J. Davies; Lloyd S. Peck (Invertebrate Reproduction & Development, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Fine-root turnover rates of European forests revisited: an analysis of data from sequential coring and ingrowth cores - I. Brunner; M. R. Bakker; R. G. Björk; Y. Hirano; M. Lukac; X. Aranda; I. Børja; T. D. Eldhuset; H. S. Helmisaari; C. Jourdan; B. Konôpka; B. C. López; et al. (Plant and Soil, 2013)

Atmospheric range correction for two-frequency SLR measurements - Dudy D. Wijaya; Fritz K. Brunner (Journal of Geodesy, 2011)

Strong Attraction of the Parasitoid Cotesia marginiventris Towards Minor Volatile Compounds of Maize - Marco D’Alessandro; Virginie Brunner; Georg von Mérey; Ted C. J. Turlings (Journal of Chemical Ecology, 2009)

Pharmacological manipulations of interval timing using the peak procedure in male C3H mice - Fuat Balci; Elliot A. Ludvig; Jacqueline M. Gibson; Brian D. Allen; Krystal M. Frank; Bryan J. Kapustinski; Thomas E. Fedolak; Daniela Brunner (Psychopharmacology, 2008)

The platform for European root science, COST action E38: An introduction and overview - D. L. Godbold; I. Brunner (Plant Biosystems, 2007)

Tree fine root Ca/Al molar ratio – Indicator of Al and acidity stress - E. I. Vanguelova; Y. Hirano; T. D. Eldhuset; L. Sas-Paszt; M. R. Bakker; Ü. Püttsepp; I. Brunner; K. Lõhmus; D. Godbold (Plant Biosystems, 2007)

Specific root length as an indicator of environmental change - I. Ostonen; Ü. Püttsepp; C Biel; O. Alberton; M. R. Bakker; K. Lõhmus; H. Majdi; D. Metcalfe; A. F. M. Olsthoorn; A. Pronk; E. Vanguelova; M. Weih; et al. (Plant Biosystems, 2007)

Variation in fine root biomass of three European tree species: Beech ( Fagus sylvatica L.), Norway spruce ( Picea abies L. Karst.), and Scots pine ( Pinus sylvestris L.) - L. Finér; H.-S. Helmisaari; K. Lõhmus; H. Majdi; I. Brunner; I. Børja; T. Eldhuset; D. Godbold; T. Grebenc; B. Konôpka; H. Kraigher; M.-R. Möttönen; et al. (Plant Biosystems, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Context and climate change: an integrated assessment for Barrow, Alaska - Amanda H. Lynch; Ronald D. Brunner (Climatic Change, 2007)

6-Alkylsalicylic Acids and 6-Alkylresorcylic Acids from Ants in the Genus Crematogaster from Brunei - T. H. JONES; S. R. BRUNNER; A. A. EDWARDS; D. W. DAVIDSON; R. R. SNELLING (Journal of Chemical Ecology, 2005)

Knowing your enemies: seasonal dynamics of host–social parasite recognition - Patrizia D’Ettorre; Elisabeth Brunner; Tom Wenseleers; Jürgen Heinze (The Science of Nature, 2004)

Wood ash treatment affects seasonal N fluctuations in needles of adult Picea abies trees: a 15 N-tracer study - M. Jggi; R. Siegwolf; M. Genenger; D. Hallenbarter; I. Brunner; J. Fuhrer (Trees, 2004)

Fine root growth and element concentrations of Norway spruce as affected by wood ash and liquid fertilisation - M. Genenger; S. Zimmermann; D. Hallenbarter; W. Landolt; E. Frossard; I. Brunner (Plant and Soil, 2003)

Special Contribution: BOHEMA 2001-2003: Passive Seismic Experiment to Study Lithosphere-Asthenosphere System in the Western Part of the Bohemian Massif - J. Plomerová; U. Achauer; V. Babuška; M. Granet; U. Achauer; V. Babu.Ka; A. Boušková; K. Bräuer; M. Brož; M. Brunner; T. Fischer; S. Funke; et al. (Studia Geophysica et Geodaetica, 2003)

Experimental oral transmission of largemouth bass virus - J E Woodland; C J Brunner; A D Noyes; J M Grizzle (Journal of Fish Diseases, 2002)
Largemouth bass virus (LMBV) is a recently discovered iridovirus that causes a fatal disease of largemouth bass, Micropterus salmoides (Lacepède). Fish can become infected by waterborne LMBV, but oral transmission of this virus has not been demonstrated previously. Largemouth bass were gavaged with guppies, Poecilia reticulata Peters, which had been injected with LMBV, and then sampled periodically during a 7‐week observation period. The dose of LMBV averaged 10 5.6 tissue culture infectious doses – 50% cytopathic endpoint (TCID 50 ) per largemouth bass. Five of 24 largemouth bass exposed to LMBV became infected with the virus, but none of the fish had clinical signs typical of LMBV disease. Virus titres in largemouth bass were highest in swim bladder (10 5.5–9.5 TCID 50 g −1 ) and were 10 5.2 TCID 50 g −1 or lower in cutaneous mucus, head kidney, trunk kidney, spleen, gonad and intestine. These results indicate that LMBV can be transmitted orally to largemouth bass, but further study is needed to determine the factors affecting pathogenicity of the virus.

Light-regulated transcription of a cryptochrome gene in the green algaMougeotia scalaris - K. D. Brunner; C. Zrb; H. . Kolukisaoglu; G. Wagner (Protoplasma, 2000)

Pharmacokinetic and pharmacodynamic effects of YM087, a combined V 1 /V 2 vasopressin receptor antagonist in normal subjects - M. Burnier; A. F. Fricker; D. Hayoz; J. Nussberger; H. R. Brunner (European Journal of Clinical Pharmacology, 1999)

Refined mapping of the gene for autosomal dominant retinitis pigmentosa (RP17) on chromosome 17q22 - A. I. den Hollander; S. D. van der Velde-Visser; Alfred J. L. G. Pinckers; Carel B. Hoyng; Han G. Brunner; Frans P. M. Cremers (Human Genetics, 1999)

A Practice‐based Approach to Ecosystem Management - Ronald D. Brunner; Tim W. Clark (Conservation Biology, 1997)
Ecosystem management is a rapidly evolving philosophy or paradigm of natural resource management intended to sustain the integrity of ecosystems. The problem is that principles of ecosystem management are unsatisfactory for practical purposes. Three major approaches to the problem are evaluated: (1) clarification of the goals of ecosystem management, (2) construction of a better scientific foundation for management decisions, and (3) comparative appraisal of current practices. The evaluation concludes that neither of the first two approaches is necessary or sufficient for better management decisions because better decisions depend upon the complexities of particular contexts. The third, practice‐based approach makes the most of the limited human capacity to cope with the complexities of ecosystem management in order to improve principles of ecosystem management, to inform particular management decisions through improved principles, and to incorporate clearer goals and a better scientific foundation as they become available. The evaluation draws on experience and disciplines beyond conservation biology and natural resource management, including policy sciences.